ESTIMASI KALENDER BUDIDAYA RUMPUT LAUT MENGGUNAKAN DATA PREDIKSI PASUT DI KAWASAN TERUMBU KARANG KEPULAUAN SERIBU BAGIAN SELATAN - Sunarto, Kris (Badan Informasi Geospasial in Partnership with MAPIN, 2009)
Commonly fishermen have other task as farmer to plant seaweed or algae. They prefer to grow algae in coralreef basin or âgobaâ, with reasons for more secure against strong waves, current and predator. Although, they often experience harvest failure, they do not realize that planting seaweed in the goba also have a big risk, especially when the sequence occurred konda. Konda is a condition where the water in the stagnant condition. If the period of konda higher than as usual, so that can lead the water quality is worse to the quality very decadent. Seaweed is the type of algae that is very sensitive to the changes in water quality areas. Konda period can not be anyone to guess and when will happen, except with taking calculation of the previous year, which is then made predictions for some years to come. The results predicted and analyzed at the going konda and the konda the occurrence of the berentetan. The results of the analysis is the basic information through the process after the analysis phase estimation can be made seaweed cultivation, called so that the planting calendar. Calendar of seaweed planting is very important to set the exact or fix for cultivation time, as well as planting sesion, the period of growth, until the harvest. Planting calendar can also be used by the entrepreneur or capitalist seeks and stability in order to avoid losses due to failed harvests.Keywords: Calendar of the planting, Seaweed cultivation.ABSTRAKPada umumnya para nelayan sebagai petani rumput laut menanam rumput laut atau alga lebih memilih lokasi di dalam suatu goba pada terumbu karang, dengan alasan lebih aman terhadap ombak, arus deras maupun predator. Walaupun sering mengalami gagal panen, mereka tidak jera dan kurang menyadari bahwa penanaman rumput laut di dalam goba juga punya resiko. Masa konda merupakan masa resiko tinggi dalam berbudidaya rumput laut, karena kualitas air laut sangat merosot. Kemerosotan tersebut berdampak pada gangguan pertumbuhan rumput laut, khususnya jenis alga yang sangat peka terhadap perubahan kualitas wilayah perairan. Masa konda tidak dapat sembarangan ditebak kapan akan terjadi. Dengan mengolah data pasang surut antara masa konda dengan yang bukan konda dapat diidentifikasi dan diklasifikasi, sehingga dapat dibuat kalender tanam untuk pembudidayaan rumput laut. Tujuan penelitian adalah untuk memperoleh informasi penting tenang jadwal pembudidayaan rumput laut yang dituangkan ke dalam bentuk kalender tanam dengan menggunakan analisis data prediksi pasang surut, untuk mendapatkan tahapan pembudidayaan.Kata kunci: Kalender tanam, budidaya Rumput laut.